EMPOWERING THE SIDO MAJU FARMERS GROUP THROUGH THE DEVELOPMENT OF A SOLAR-POWERED CORN THRESHER - Ekoanindiyo, Firman Ardiansyah; Kasmari, Kasmari; Eniyati, Sri; Hayati, Enty Nur (Universitas katolik Musi Charitas, 2024)
This community service initiative seeks to enhance the design of a corn thresher to improve its functionality and expand its market potential. The activities include field inspections, discussions, training, and socialization with village officials, expert teams, and farmers' groups. Previous designs revealed several shortcomings, such as an intake hole positioned too high, causing user discomfort, and a small diameter that made it challenging to process larger corn cobs. Additionally, the separation mechanism between cobs and kernels was ineffective, leading to mixed results. Farmers also struggled with marketing their crops, often relying on traders visiting the village, which resulted in lower selling prices. The redesigned thresher addresses these issues by enabling upright operation, increasing intake capacity, and reducing costs through solar power. Complementing the redesign, online marketing training equips farmers with strategies to align their prices with market standards, reduce dependence on intermediaries, and enhance their income sustainably.